2013
DOI: 10.1155/2013/370828
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Jordanian Psychiatric Nurses’ Smoking Behaviors: A Grounded Theory Study

Abstract: Purpose. Smoking is prevalent in psychiatric facilities among staff and patients. However, there have been few studies of how contextual factors in specific cultures influence rates of smoking and the health promotion role of psychiatric nurses. This paper reports the findings of a classical grounded theory study conducted to understand how contextual factors in the workplace influences the smoking behaviors of Jordanian psychiatric nurses (JPNs). Method. Semi-structured individual interviews were conducted wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 35 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…These findings are supported by other studies [ 6 , 9 ] which found that nurses do not meet the recommended levels of physical activity required for the benefit of health (30 minutes, 5 days a week). Other behavioural risk factors that have been identified among nurses include smoking and alcohol abuse [ 11 - 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings are supported by other studies [ 6 , 9 ] which found that nurses do not meet the recommended levels of physical activity required for the benefit of health (30 minutes, 5 days a week). Other behavioural risk factors that have been identified among nurses include smoking and alcohol abuse [ 11 - 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the United States, Australia and New Zealand have long implemented smoke-free environments, compliance has been lower in Central and Eastern Europe countries and Jordan (Khalaf et al, 2017;Petersen et al, 2019). Also, smoking among health professionals was still seen as a common behaviour in psychiatric health settings (Aldiabat & Clinton, 2013). Many studies described how nurses were less likely to support the implementation of smoke-free policies.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, they were happy to see patients enjoying a cigarette which 'reduced the negative impacts of their illness', but on the other hand they were aware that this contravened the rules. They described 'widespread tolerance' of smoking and the distribution of cigarettes to patients as being 'institutionalized' (Aldiabat & Clinton, 2013;Lawn & Condon, 2006).…”
Section: Hypocrisy and Guiltmentioning
confidence: 99%
See 2 more Smart Citations